Cd40 doesn't Complement The Function Of Epstein-barr Virus (Ebv) Latent Membrane Protein 1 In B Cells Transformation - Ahsan, Mohammed Nazmul; Akhand, Anwarul A (Bangladesh Journal of Medical Science, 2012)
Objective: EpsteinBarr virus (EBV) latent membrane protein 1 (LMP1) is known to plays important role in B cells growth and transformation. LMP1 is considered to be a functional homologue of the CD40 receptor and they can activate many overlapping signaling pathways. In this study, we compared the function of CD40 with that of LMP1 in B cells transformation. Materials and methods: Expression of CD40L was observed in infected B cells with LMP1 mutated EBV. To observe the expression reverse transcription-PCR were performed. Results: This expression of CD40L did not support proliferation and transformation of B cell. Even in vitro proliferation and transformation of B cell infected with LMP1 deleted EBV supplemented with CD40L were also not observed. Conclusion: Despite many similarities shared between CD40 and LMP1, CD40-CD40L interaction didnt complement on LMP1 mediated B cells transformation in vitro. DOI: http://dx.doi.org/10.3329/bjms.v11i2.8175 Bangladesh Journal of Medical Science Vol. 11 No. 02 April 2012: 112-116